2010
DOI: 10.1057/jt.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of fashion clothing involvement among Indian youth

Abstract: In developing countries, consumers are becoming conscious of fashion brands. The research was directed towards understanding the determinants of fashion clothing involvement of Indian youth. A primary research study was conducted on Indian college students aged between 18 and 24 years using the fashion clothing involvement scale developed by O ' Cass to understand the importance of fashion clothing in their lives. The scale had constructs related to consumption involvement, product involvement, advertising inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 66 publications
3
41
0
1
Order By: Relevance
“…The results support earlier research on fashion clothing involvement in India that clothes help consumers to improve self-identity. 33 The rising income levels and accessibility to global brands has affected Indian consumers ' evaluation and consumption of fashion brands. Fashion clothing connotes status and consequently enables consumers to enhance their self-image.…”
Section: Discussionmentioning
confidence: 99%
“…The results support earlier research on fashion clothing involvement in India that clothes help consumers to improve self-identity. 33 The rising income levels and accessibility to global brands has affected Indian consumers ' evaluation and consumption of fashion brands. Fashion clothing connotes status and consequently enables consumers to enhance their self-image.…”
Section: Discussionmentioning
confidence: 99%
“…The study considers the effects of various factors influencing on purchase intention including consumers' personal characteristics such as age, gender, income as well as some external factors including advertisement. The study uses a questionnaire in Likert scale, originally developed by O'Cass (2000O'Cass ( , 2004 and Khare and Rakesh (2010). The study considers the following six hypotheses, which are also shown in Fig.…”
Section: The Proposed Studymentioning
confidence: 99%
“…In addition, Wang and Wang (2010) revealed that women were more concerned about their physical appearance than were men. Males' and females' perceptions of fashion and what it connotes may differ as well (Khare & Rakesh, 2010). Generally, fashion is seen as an integral part of women's personality; therefore, women are better equipped than men to understand fashion clothing and their choice of apparel fashion is based on current trends (McCraken & Roth, 1989).…”
Section: Gender Effects On Mobile Shopping Intentionmentioning
confidence: 99%